2000
DOI: 10.1021/ja001638d
|View full text |Cite
|
Sign up to set email alerts
|

Noncovalent Interactions of Nucleic Acid Bases (Uracil, Thymine, and Adenine) with Alkali Metal Ions. Threshold Collision-Induced Dissociation and Theoretical Studies

Abstract: Threshold collision-induced dissociation of M + L (M + ) Li + , Na + , and K + ; L ) uracil, thymine, and adenine) with xenon is studied using guided ion beam mass spectrometry. In all cases, the primary product formed corresponds to endothermic loss of the intact neutral molecule. The only other product observed is the result of ligand exchange processes to form MXe + . Cross-section thresholds are interpreted to yield 0 and 298 K bond dissociation energies for M + -L after accounting for the effects of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

46
312
5

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(370 citation statements)
references
References 67 publications
46
312
5
Order By: Relevance
“…Note that such a complete metal reduction process was observed neither with copper nor with calcium. Interaction of alkali metal M ϩ towards uracil [33] and thiouracil [15] derivatives has been also explored, and bond dissociation energies for Li ϩ , Na ϩ and K ϩ have been determined. The metal-ion [M(SU)] ϩ complexes exhibit similar behavior upon CID, characterized by the loss of the intact neutral nucleobase.…”
Section: Low-energy Cid Spectra Of [Pb(thiouracil)mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that such a complete metal reduction process was observed neither with copper nor with calcium. Interaction of alkali metal M ϩ towards uracil [33] and thiouracil [15] derivatives has been also explored, and bond dissociation energies for Li ϩ , Na ϩ and K ϩ have been determined. The metal-ion [M(SU)] ϩ complexes exhibit similar behavior upon CID, characterized by the loss of the intact neutral nucleobase.…”
Section: Low-energy Cid Spectra Of [Pb(thiouracil)mentioning
confidence: 99%
“…We studied mono-and bi-coordination modes and we considered that deprotonation could occur on several sites: nitrogens, C(5), and oxygens or sulfurs for tautomeric forms. We decided not to investigate in detail -interactions because of the resulting distortion of the ring from planarity, which destroys the resonance delocalization and leads to high-energy species [33,41]. Relevant bond lengths of the most stables structures obtained are given in Figure 3.…”
Section: Structures and Relative Stabilities Of [Pb(thiouracil) ϫ H]mentioning
confidence: 99%
“…In the former case, the mass spectra should ideally directly represent the solution phase chemistry. Gas-phase methods include cone voltage driven dissociation (called the "VC 50 " method) [12,13], collision-induced dissociation [14,15], guided ion beam tandem mass spectrometry [16,17], blackbody infrared radiative dissociation [18,19] and heated capillary dissocation [20,21].…”
mentioning
confidence: 99%
“…The affinities of alkali-metal ions with nucleobases have been investigated by both the kinetic method and threshold collision-induced dissociation mass spectrometry [2,3]. On the basis of the research work on the formation of gas-phase ion-molecule complexes, Fujii [4] concluded that the alkali-metal ion affinity generally followed the order of Li ϩ Ͼ Na ϩ Ͼ K ϩ .Various mass spectrometric methods have been used to characterize metal ion biomolecular interaction at the molecular level, to determine the site of metal ion attachment to the biomolecular and its effect on altering the properties and reactivities of the biomolecule [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. ESI-MS was shown to be an excellent means for characterizing of oligonucleotides [18,19], and provide unambiguous identification of singly and multiplycharged ions of deprotonated, protonated, and metalated oligonucleotides.…”
mentioning
confidence: 99%
“…Alkali-metal ion affinities are a good basis for analysis and modeling of such interactions in complex systems. The affinities of alkali-metal ions with nucleobases have been investigated by both the kinetic method and threshold collision-induced dissociation mass spectrometry [2,3]. On the basis of the research work on the formation of gas-phase ion-molecule complexes, Fujii [4] concluded that the alkali-metal ion affinity generally followed the order of Li ϩ Ͼ Na ϩ Ͼ K ϩ .…”
mentioning
confidence: 99%